High-fidelity photometry and astrometry of high-contrast imaged companions using LOCI processing. Issue Volume 8:Issue S299(2013) (6th January 2014) - Maire, Jérôme; Gagné, Jonathan; Lafrenière, David; Graham, James R.; Doyon, René
Résumé: Direct imaging and spectroscopy of exoplanets is a key element for understanding planet formation and migration. Such direct detections and characterizations remains technologically challenging, since a very high contrast ratio and small angular separation are involved, and futhermore speckle noise limits the high-contrast imaging performance. We further discuss a speckle subtraction and suppression technique that fully takes advantage of spectral and time-domain information on quasi-static speckles to measure the highest-fidelity photometry as well as accurate astrometry of detected companions.